2009
DOI: 10.24191/smrj.v6i2.5177
|View full text |Cite
|
Sign up to set email alerts
|

Measuring website service quality for Malaysian companies

Abstract: A customer-perceived quality service has been widely used towards enhancing the customers’ satisfaction and loyalty. The same situation is also applicable for the online services; in an increased use of websites as a channel for information presentation and provision of other services. Hence, the website service quality perceptions of users need to be understood so as to be managed more effectively. The key dimension of this study is to identify the website service quality through the qualitative and quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 9 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…Website quality is a multi-dimensional concept. Past research identified four dimensions of website quality as technical adequacy, the appearance and visual appeal of the website, the quality content and specific content related to products, customer support and privacy (Voon et al , 2009). Website quality dimensions could also be security, enjoyment, information quality, ease of use and service quality (Hasanov and Khalid, 2015).…”
Section: Development Of Hypothesesmentioning
confidence: 99%
See 4 more Smart Citations
“…Website quality is a multi-dimensional concept. Past research identified four dimensions of website quality as technical adequacy, the appearance and visual appeal of the website, the quality content and specific content related to products, customer support and privacy (Voon et al , 2009). Website quality dimensions could also be security, enjoyment, information quality, ease of use and service quality (Hasanov and Khalid, 2015).…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…(Kumar and Hasteer, 2017). In addition to the technical quality, information on websites has to be well-organized (Voon et al , 2009). Firms’ financial outcomes such as profitability could increase if they provide sufficient corporate information on their websites and show consideration for stakeholders’ experiences (Na et al , 2019; Homayoun and Rahman, 2010).…”
Section: Development Of Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations